Kompetensi Profesional Calon Guru PAUD dalam Meningkatkan Kualitas Pembelajaran: Sistematis Literatur Review: Professional Competence of Prospective PAUD Teachers in Improving the Quality of Learning: Systematic Literature Review - Sofwatul, Lilik Sofwatul Mala; Hibana; Suyadi (Universitas Ngudi Waluyo, 2025)
One of the most important qualities that prospective PAUD teachers must have to encourage the development of high-quality learning is professional competence. Using a literature review study approach, this study seeks to investigate and evaluate how the professional competence of future PAUD teachers contributes to improving teaching standards. This study collects and examines various related literature, such as Google Scholar, OpenKnwledge, Sage, and ScienceDirect. Focusing on literature published in the last 10 years, namely between 2015 and 2024. This study will be conducted in three stages, starting with a literature search using the keywords